2002
DOI: 10.1097/00005373-200211000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Blunt Trauma Patients with Prehospital Pulseless Electrical Activity (PEA): Poor Ending Assured

Abstract: If these grim results are corroborated by other investigators, consideration should be given to allowing paramedics to declare blunt trauma victims with PEA dead at the scene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…This is in agreement with Martin et al (5), who suggested that initial rhythm (pulseless electrical activity) in trauma is probably not a robust predictor of patient outcome. Therefore, we think that trauma patients in cardiac arrest need active resuscitation in the field until they regain cardiac activity instead of quick transportation to a trauma center, especially if the transport will last for Ͼ15 mins (6).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in agreement with Martin et al (5), who suggested that initial rhythm (pulseless electrical activity) in trauma is probably not a robust predictor of patient outcome. Therefore, we think that trauma patients in cardiac arrest need active resuscitation in the field until they regain cardiac activity instead of quick transportation to a trauma center, especially if the transport will last for Ͼ15 mins (6).…”
Section: Discussionsupporting
confidence: 92%
“…Despite advances in medical care, survival rates of 0% to 2% have been consistently reported for blunt trauma patients who arrive at a trauma center with no signs of life (2)(3)(4)(5)(6). Unfortunately, many of these survivors experience severe permanent neurologic disability (5,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 Martin et al reported 110 BCR patients with prehospital PEA, concluding that the chance of survival diminishes if a patient develops prehospital cardiac arrest or PEA. 9 Clinical manifestations depend on the presence or absence of tear in the pericardium. Intact pericardium after BCR can result in cardiac tamponade whilst tear in pericardium often presents with haemothorax and haemorrhagic shock in a small percentage of patients (10%).…”
Section: Discussionmentioning
confidence: 99%
“…SpO 2 climbed to 80% and the patient regained spontaneous Unrecognized esophageal intubation is frequent [1], and traumatic PEA resuscitation is often futile [2], so there are 3 messages we want to address:…”
Section: Accepted M Manuscriptmentioning
confidence: 99%